Empirical Study on the Analysis of the Financial Auditor's Concern in Ensuring the Transparency and Sustainable Performance of BSE Listed Companies - Maria GROSU; Costel ISTRATE; Ioan Bogdan ROBU (Audit Financiar, 2023)
Sustainable development of the company implies achieving a balance in terms of economic, social and environmental activities with the aim of making optimal use of the entity's resources without harming the environment and through an active involvement of the company in society. To this end, an important role is played by the financial auditor, the guarantor of transparency in financial reporting and an active player in enforcing discipline in sustainable reporting. Through the audit report, including the opinion expressed, the auditor contributes to the credibility of the audited financial statements and inspires confidence in all users. The purpose of this study is to test the influence of the audit opinion and the auditor's membership of the Big4 group of companies on key indicators of financial position and performance, as well as on the use of performance management operations. The study also tested the influence of the audit opinion, in conjunction with the influence of key financial indicators, on the probability of reporting Key Audit Matters (KAM) related to earnings management operations or going concern. The study was conducted at the level of Romanian companies listed on the Bucharest Stock Exchange (BSE) - Regulated Market, in the period 2012-2022. Using advanced statistical methods of data analysis, the main results of the study indicate the existence of a significant influence of the previous year's audit opinion expressed by a particular type of auditor on key indicators of financial position and performance, as well as on discretionary accruals. At the same time, the prior year audit opinion as well as the current year values of the key financial indicators analysed have a significant influence on the probability of reporting on Key Audit Matters (KAM) related to earnings management operations or going concern.